Correction: Factors affecting health information resources in central libraries at Iranian universities of medical sciences - Tayebeh Khajeh; Alireza Isfandyari Moghaddam; Behrooz Bayat; Fariborz Doroudi (Tabriz University of Medical Sciences, 2023)
This corrects the article "Factors affecting health information resources in central libraries at Iranian universities of medical sciences" published in 2022: Volume 11, page 18 (doi: 10.34172/ rdme.2022.018). The first affiliation in the original version has not been written in the correct format. This has now been corrected in the PDF and HTML versions of the article.